COMPARATIVE LEGAL ANALYSIS OF RENEWABLE ENERGY UTILIZATION REGULATIONS BETWEEN ICELAND AND INDONESIA - Alghasi, Muhammad Ansy; Althafzufar, Muhammad Ansy (Transpublika Publisher, 2024)
Renewable energy has emerged as a pivotal aspect in addressing both energy security and climate change concerns. Iceland stands out as a notable exemplar in effectively harnessing renewable energy, with nearly 100% of its electricity demands met through renewable sources by 2023. In contrast, Indonesia is in the process of capitalizing on its abundant renewable energy potential, with renewables constituting only 12.5% of its electricity generation in the same year. This study undertakes a comparative analysis of the regulatory frameworks governing renewable energy utilization in Iceland and Indonesia, focusing on legal dimensions. Employing a comparative methodology with a normative juridical approach, data were gathered through literature review and examination of pertinent legal documentation. The findings underscore Iceland's robust and coherent regulatory structure supporting renewable energy utilization, characterized by clearly defined policies, incentivizing mechanisms, and efficient institutional frameworks. Conversely, Indonesia's regulatory landscape reveals a need for greater cohesion and harmonization, marked by fragmented policies, limited incentives, and suboptimal institutional arrangements. Noteworthy disparities between the two countries are attributed to factors such as political commitment, geographical considerations, and technological capacities. The research highlights the potential for Indonesia to draw valuable lessons from Iceland's experiences in formulating conducive regulations for renewable energy utilization. Key areas for improvement include bolstering policy frameworks, enhancing incentivization measures, and streamlining institutional mechanisms. By contributing insights into renewable energy regulations, this study offers guidance for policymakers in Indonesia towards optimizing the utilization of renewable energy resources.